Classroom behaviour : a practical guide to effective teaching, behaviour management and colleague support - Mishra, R. C. (New Delhi : A P H pubshing co, 2010)
The book explores this issue in a comprehensive manner, and gives various strategies and tips to inculcate a sense of positive classroom behaviour. Designed to meet the needs of both teachers and students, it provides the reader highly useful pointers
Includes bibliographical references and index.
Keywords: Classroom management; Teacher effectiveness